The Influence of Brand Image on Purchasing Decision Making at UD Serlin Gido District Nias Regency - Halawa, Fanotona; Laia, Otanius; Harefa, Idarni; Bate'e, Maria Magdalena (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study investigates the influence of brand image on consumer purchasing decisions at UD. Serlin, a trading company in Gido District, Nias Regency, Indonesia. The research was driven by the increasingly intense competition in the trading sector, which requires businesses to establish a strong brand image to maintain customer loyalty. A quantitative associative method was applied with a population of 175 consumers, from which a sample of 35 respondents (20%) was selected. Data were collected using a Likert-scale questionnaire and analyzed through validity and reliability tests, normality and heteroskedasticity tests, simple linear regression, t-test, and the coefficient of determination (R²) using SPSS 24. The findings revealed that all instruments were valid and reliable, the data were normally distributed, and no heteroskedasticity issues were detected, ensuring the regression model was feasible. The t-test yielded a significance value of 0.000 (<0.05), indicating that brand image significantly influences purchasing decisions. The coefficient of determination (R²) of 0.701 suggests that brand image explains 70.1% of purchasing decision variance, with the remaining 29.9% influenced by other factors. The study concludes that strengthening brand image is crucial for enhancing purchasing decisions. Companies should improve service quality and reinforce brand identity to sustain competitiveness.